2002
DOI: 10.1007/s100080100244
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and electrochemical investigation of boron-doped mesocarbon microbead anode materials for lithium ion batteries

Abstract: The structure and anodic performance of boron-doped and undoped mesocarbon microbeads (MCMBs) have been comparatively studied and the results obtained by XPS, XRD, SEM, Raman spectroscopy and electrochemical measurements are discussed. It is found that boron doping introduces a depressed d(002) spacing and the larger amount of "unorganized carbon", which induces vacancy formation in the graphite planes and leads to a quite different morphology from that of the undoped material. Electrochemical charge/discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Among the new materials studied, multi-walled carbon nanotubes (MWNTs) are of special interest since they combine structural features of graphite and fullerenes and open up different ways of intercalation with foreign atoms and molecules [5][6][7]. Recent research on carbon nanotubes used as anode material for lithium-ion batteries has shown that the electrochemical intercalation/ de-intercalation of lithium into/from this unique material is reversible and promising [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the new materials studied, multi-walled carbon nanotubes (MWNTs) are of special interest since they combine structural features of graphite and fullerenes and open up different ways of intercalation with foreign atoms and molecules [5][6][7]. Recent research on carbon nanotubes used as anode material for lithium-ion batteries has shown that the electrochemical intercalation/ de-intercalation of lithium into/from this unique material is reversible and promising [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…TiN-C nanoparticles were synthesized using TiCl 4 and NaN 3 reactants in supercritical benzene medium that also serves as a carbon source and, afterward, applies heat treatment under NH 3 and N 2 atmospheres. The evolutions of carbon phase during supercritical process and following heat treatments were studied extensively.…”
Section: Resultsmentioning
confidence: 99%
“…However, their poor rate capability and cycling performance, because of failure of carbon structure, cannot meet the upward requirements for high-performance LIBs [2,3]. Recently, there have been tremendous e orts to improve carbonaceous anodes performance by doping various elements as conducting agent or decreasing crystallite size and increasing pore structure [3,4]. Using active-inactive composites as a mixedconductive matrix, which electrically isolates the active particles from the current collector, is one of the solutions to improve the anode performance.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of choosing longer or shorter relaxation durations and their position in a complete cycle (i.e., whether to relax before or after discharge) over cell performance is also unclear. By conducting a parametric study on relaxation ('resting') effect for O (10 3 ) cycles for Li-ion cells, we intend to fulfill the following objectives in this work:…”
Section: A3146mentioning
confidence: 99%